Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please could someone help me and see if my solutions are correct for these two limits

Let $n \in \mathbb{N}$ and $y \in \mathbb{R}$ and $y>0$.

Case 1 $$\lim_{y \to \infty} \cfrac{y^n}{y^{n+1}}=\lim_{y \to \infty} y^{n-(n+1)}= \lim_{y \to \infty} \cfrac{1}{y}=0$$

Case 2 $$\lim_{n \to \infty} \cfrac{y^n}{y^{n+1}}$$

In this case, I consider that I cannot manipulate the exponents in the same way as in case 1. So let be

Case 2

$$L = \lim_{n \to \infty} \cfrac{y^n}{y^{n+1}}$$

$$\sqrt[n]{L} = \sqrt[n]{\lim_{n \to \infty} \cfrac{y^n}{y^{n+1}}}=\lim_{n \to \infty} \sqrt[n]{\cfrac{y^n}{y^{n+1}}}=\lim_{n \to \infty} \cfrac{y^{n/n}}{y^{(n+1)/n}}$$

$$\sqrt[n]{L} = \lim_{n \to \infty} \cfrac{y^{1}}{y^{1+1/n}}=1$$

And thus,

$$ L = 1^n = 1$$

share|cite|improve this question
The first step you have done is just algebra, it has nothing to do with limits. So certainly you can do it the same way in case 1 and case 2. – David Feb 25 '14 at 23:05
@David I don't think so. Algebra works quite nice when you do not involve $\infty$. In some way, I am asking $\lim_{n \to \infty}n-(n+1)$. Or also $\infty - \infty$?. – Erivelton Geraldo Nepomuceno Feb 25 '14 at 23:14
I'm only talking about the first step. This is before you take the limit and therefore it does not involve $\infty$. – David Feb 25 '14 at 23:23

No, for all positive n, case 2 is the constant 1/y. Why the doubt that you cannot "manipulate the exponents in the same way"?

For all n, $\frac{y^n}{y^{n+1}} = \frac{1}{y}$. To convince yourself of this, plug in say, 2 for n, then plug in 3, then plug in 4 etc. But you could just as easily write $\frac{y^n}{y^{n+1}} = \frac{1}{y^{(n + 1) - n}} = \frac{1}{y}$.

To see the error in the "proof" take the n-th root of any positive number C and then take the limit:

$$\lim_{n \to \infty} \sqrt[n]{C} = 1$$

And for all n, $$1^{n} = 1$$

Nevertheless, this does not prove that C = 1. (In your case 2, C is 1/y.)


What the above argument shows is that taking the limit of the n-th root of any positive number destroys all information on what postive number you started with. Similarly, multiplying a number by zero destroys all infomation on what number you started with. Taking the n-th root and raising to the n-th power are inverses of each other, but not if you take limits in between.

Also, I agree that Case 1 is perfectly fine.

Another edit:

The particular part that is incorrect is that in fact,

$$\sqrt[n]{\lim_{n \to \infty} \cfrac{y^n}{y^{n+1}}} \neq \lim_{n \to \infty} \sqrt[n]{\cfrac{y^n}{y^{n+1}}}$$

The problem is that the $n$ outside of the limit and the $n$ inside are different. The one on the outside is a fixed number (it doesn't approach infinity). But once it is put inside the limit, it is no longer fixed. The n underneath the limit is a dummy variable. i.e.,

$$\lim_{n \to \infty} \frac{y^n}{y^{n+1}} = \lim_{j \to \infty} \frac{y^j}{y^{j+1}}.$$

It is true that

$$\sqrt[n]{\lim_{j \to \infty} \frac{y^j}{y^{j+1}}} = \lim_{j \to \infty} \sqrt[n]{\frac{y^j}{y^{j+1}}}$$

but then we see that the n and the j do not simplify.

share|cite|improve this answer
Let $p=n$ and $k=n+1$ $$ \lim_{n \to \infty} \cfrac{p}{k} = \lim_{n \to \infty} \cfrac{n}{n+1} = \lim_{n \to \infty} \cfrac{n}{n+1}\cfrac{\frac{1}{n}}{\frac{1}{n}} = \lim_{n \to \infty} \cfrac{1}{1+\frac{1}{n}} =1$$ That is $$ \lim_{n \to \infty} \cfrac{p}{k} =1 $$ $p/k$ goes to $1$ if and only if $p-k$ goes to $0$. Case 2 $$ \lim_{n \to \infty} \cfrac{y^p}{y^k} = \lim_{n \to \infty} y^{p-k} =\lim_{n \to \infty} y^{0} = 1 $$ The result $1/y$ implies that $p/k$ does not go to $1$, which seems to me that contradicts the notion of infinity. @David ? – Erivelton Geraldo Nepomuceno Feb 26 '14 at 5:19
No, the statement p/k goes to 1 iff p-k goes to 0 is false. Let f(n) = n^2 + n and g(n) = n^2. Then f(n) - g(n) approaches infinity. Yest still f(n)/g(n) approaches 1. In your case, p-k is the constant 1. – Andrew Kelley Feb 26 '14 at 21:56
Oops. p-k is the constant -1. – Andrew Kelley Feb 27 '14 at 23:11
Dear @AndrewKelley, I am not confident with this reasoning. I found this affirmation in "Cauchi's Cours d'analyse": When variables remain independent, the values of $x/y = 0/0 = M((- \infty, + \infty))$ or $x/y = \infty / \infty =-\infty /- \infty= M((0,+ \infty))$. When I take $y^n$ I mean a function independent of $y^{(n+1)}$. And therefore, for $y<1$, it would be $M((-\infty,+ \infty))$ and for $y=1$, it would be $1$, and for $y>1$ it will be $M((0,+ \infty))$. Where $M((a,b))$ denotes any value betwen the limits of $a$ and $b$. What do you think? – Erivelton Geraldo Nepomuceno Feb 28 '14 at 13:46
I like your approach when you use destroy the information. I also think that when someone just cancel terms $n$ from two different functions, I think it would be also destroying the information about the individuality of each function. @andrew-kelley – Erivelton Geraldo Nepomuceno Feb 28 '14 at 13:53

Looks good.

For case 1, the denominator grows faster and thus the limit goes to 0.

The second case is wrong however. It can be simplified like this:

$$\lim_{n \to \infty} \frac{y^n}{y^{n+1}} = \lim_{n \to \infty} \frac{1}{y} = \frac{1}{y}$$

In other words, you can use the same method as for case 1.

share|cite|improve this answer
Thank you. Let us see if other guys accord with my additional argument. What do you think? – Erivelton Geraldo Nepomuceno Feb 26 '14 at 5:23
After reading the other answer I realised I was wrong about case 2. I've changed the details now. – naslundx Feb 28 '14 at 18:22
Did you add something else? @naslundx – Erivelton Geraldo Nepomuceno Mar 1 '14 at 5:46

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.